HISTORY OF ACUTE PROMYELOCYTIC LEUKEMIA: A TALE OF ENDLESS REVOLUTION - Laura Cicconi; Francesco Lo-Coco (Mediterranean Journal of Hematology and Infectious Diseases)
Only few thousand people are diagnosed each year of Acute Promyelocytic Leukemia (APL) worldwide. However, for a number of reasons such rare disease is regarded as a paradigm in the entire field of medicine. Once considered the most malignant human leukemia as well as the one associated with the worst prognosis, APL has been transformed in the past few decades into the most frequently curable one. This extraordinary progress has been the result of an unprecedented coincidence of advances in both biological and clinical research.